2014
DOI: 10.1002/poc.3347
|View full text |Cite
|
Sign up to set email alerts
|

Bond dissociation energies in organometallic systems: substituent effects

Abstract: A knowledge of the factors determining the magnitude of the bond dissociation enthalpy (BDE) is of importance to the advancement of theoretical organometallic chemistry and from the practical standpoint. The central atom and the substituents bound to it influence the BDE values; however, the interplay between the BDE and the substituent effects remains unknown. In this work, the literature data on substituent influence on the BDE of lithium, sodium, copper, silver, mercury, aluminium, gallium, silicon, germani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Direct evidence for the influence of polarizability effect is the statistical significance of the coefficient c for all series I–XLII. Thus, we found that this effect influences the properties of any complexes, including weak ones, as predicted earlier. All complexes have 1 feature in common consisting in electron density transfer from donor center (or fragment) to the acceptor one.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Direct evidence for the influence of polarizability effect is the statistical significance of the coefficient c for all series I–XLII. Thus, we found that this effect influences the properties of any complexes, including weak ones, as predicted earlier. All complexes have 1 feature in common consisting in electron density transfer from donor center (or fragment) to the acceptor one.…”
Section: Resultssupporting
confidence: 87%
“…It is remarkable that the properties scriptP of nonclassic series do not obey the Equation , and hence intramolecular interactions in classic and nonclassic charged series differ considerably. This distinction is caused by the influence of the polarizability effect on the chemical and physical properties of nonclassic series, in particular, on the parameters of the IR, NMR, UV‐Vis, Mössbauer, and NQR spectra of complexes as well as on the bond lengths and bond dissociation enthalpies of different complexes.…”
Section: Calculation Proceduresmentioning
confidence: 99%